Iranian Pediatric COVID-19 Epidemiology and Clinical Characteristics - Shahnaz Armin; Mohammadreza Mirkarimi; Zahra Pourmoghaddas; Marjan Tariverdi; Azadeh Jafrasteh; Noushin Marhamati; Armin Shirvani; Abdollah Karimi; Sedigheh Rafiei Tabatabaei; Roxana Mansour Ghanaei; SeyedAlireza Fahimzad; Fariba Shirvani; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Despite the worldwide spread of Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2), information about the epidemiological and clinical patterns of this infection is still largely unknown in children. In addition, the prevalence of this disease is still very high in some parts of the world, including Iran. Thus, this study aims to evaluate the epidemiological features, laboratory and imaging findings, and the type of treatments in children with novel coronavirus 2019 (COVID-19). Method. This study is conducted from March 2020–March 2021 by using the medical records of hospitalized confirmed COVID-19 children younger than 18 years in five cities of Iran: Tehran, Ahwaz, Isfahan, Bandar-Abbas, and Khorramabad. In addition to demographic and epidemiological data, we also studied clinical signs and treatments. Results. In total 278 confirmed COVID-19 children, the average age was 5.3 years, and 59.4%were boys. A total of 37.8% had an underlying disease, in which the most common was a malignancy. The most common symptoms were fever and cough. In this group of pediatrics, some abnormal laboratory findings have been seen. GGO (Ground-Glass Opacity) had been diagnosed in 58.6% of children. 3.6% needed oxygen therapy with ventilators, and 83.09% had received antibiotic treatments with the majority of ceftriaxone. Also, 10% had got steroids. In this study, the mortality rate was 4.3%. Conclusion. In this study, most of the children who died had an underlying disease, so timely care and action is important in them. Most children admitted to our study received antibiotics and were prescribed antivirals and steroids for a smaller number. Also, a small number of children received oxygen therapy, most of whom were in the age group of 1 to 5 years.